Effect of Fermentation and Malting on the Viscosity of Maize-Soyabean Weaning Blends - Amankwah, E.A.; Barimah, J.; Acheampong, R.; Addai, L.O.; Nnaji, C.O. (Pakistan Journal of Nutrition, 2009)
Weaning foods made from cereals and legumes are used in solving the problem of malnutrition in infants; however, the bulky nature of the porridge discourages many infants from consuming it. In order to improve the dietary bulk of weaning foods, the effects of fermentation and malt addition on the viscosity of maize-soyabean blends were studied. The material balance method was used to target 18% protein and 59% carbohydrate in the weaning formulation. This method was used to achieve the control blend of 70% maize flour and 30% soyabean flour. The rest of the blends were formulated by adding either 5% (M 5) or 10% (M 10) malt to the Unfermented (UF), 2 days fermented (F2) and 3 days fermented maize flour (F3) and mixing each with 30% Soyabean Flour (S). Chemical analysis conducted on the flours showed soyabean flour had the highest protein content of 42.61% and the unfermented maize flour had the highest carbohydrate value of 74.57%. Results of viscoamylography of the various blends showed that M0F2S recorded a higher setback viscosity than the control but blends M5F3S, M10F2S and M10F3S provided porridges that were less viscous. Increase in viscosity as fermentation time increased was due to the increase in the protein, crude fibre and fat during fermentation. Generally, malting alone led to a reduction in product viscosity but fermentation led to an increase. However, the cumulative effect of fermentation and malting with the addition of malt after the fermentation reduced viscosity.